Spiritual Status Related to Life Quality Of Elderly - Mujib Hannan; Syaifurrahman Hidayat (Wiraraja Medika : Jurnal Kesehatan, 2020)
ABSTRACT Good spiritual owned by the elderly will help them in maintaining the relationship with God, people around, and environment, so that they can realize and know the purpose of life in the future. Elderly suffer from various health problems due to the vulnerability of many physical and mental disorders. Quality of life in the elderly can be influenced by many environmental factors. Quality of life tends to be good when the physical and psychological conditions are healthy and functioning properly. The research method used analytic correlation with cross-sectional design, the population in this study was the elderly who were more than 45 years old, the sampling technique was Simple Random Sampling with 83 samples. Analysis technique to determine the relationship betwen spiritual status with quality of life of the elderly used Spearman test. The results of this study said that most of the respondents' spiritual status can be categorized as high as 48 people (57.8%) and most of the quality of life of respondents can be categorized as good as 46 people (55.4%). In other words, it can be concluded that Spearman Rho test results indicated that Significancyp value = 0.004 (p <0.005). For the result, it means that there was a relationship between spiritual status and quality of life of elderly. Quality of life is a humans’s subjective feelings about their well-being, based on their current life experience, in which spiritual significantly is able to help the elderly and provide services to adapt with changes caused by chronic disease. Keywords: spiritual status, life quality, elderly